2022
DOI: 10.1038/s41598-022-11208-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of hepatitis E virus (HEV) in imported and domestic camels in Saudi Arabia

Abstract: Camels gained attention since the discovery of MERS-CoV as intermediary hosts for potentially epidemic zoonotic viruses. DcHEV is a novel zoonotic pathogen associated with camel contact. This study aimed to genetically characterize DcHEV in domestic and imported camels in Saudi Arabia. DcHEV was detected by RT-PCR in serum samples, PCR-positive samples were subjected to sequencing and phylogenetic analyses. DcHEV was detected in 1.77% of samples with higher positivity in domestic DCs. All positive imported dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
(36 reference statements)
0
14
1
Order By: Relevance
“…13.4%) (El-Kafrawy et al, 2020). Similarly, a study conducted in Saudi Arabia found that all infected camels tested with RT-PCR were male (El-Kafrawy et al, 2022). Although our findings support the influence of gender on HEV infection in dromedary camels, some studies such as Li et al (2017) and Ouoba et al (2019) have not found any association between gender and HEV infection (Li et al, 2017;Ouoba et al, 2019).…”
Section: Discussioncontrasting
confidence: 64%
“…13.4%) (El-Kafrawy et al, 2020). Similarly, a study conducted in Saudi Arabia found that all infected camels tested with RT-PCR were male (El-Kafrawy et al, 2022). Although our findings support the influence of gender on HEV infection in dromedary camels, some studies such as Li et al (2017) and Ouoba et al (2019) have not found any association between gender and HEV infection (Li et al, 2017;Ouoba et al, 2019).…”
Section: Discussioncontrasting
confidence: 64%
“…Animal reservoirs of HEV infection include rabbits, deer, pigs, and wild boars [ 52 , 53 , 54 , 55 , 56 ]. Zoonotic transmission of HEV to humans is documented to occur through several animal species including pigs, rabbits, wild boars, camels, bats, and goats [ 8 , 9 , 14 , 18 , 54 , 55 , 57 , 58 ]. While dromedary camels were reported to be infected with HEV genotype 7 [ 14 , 15 ], their potential to transmit the infection to humans was only reported in a single case from the United Arab Emirates [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zoonotic transmission of HEV to humans is documented to occur through several animal species including pigs, rabbits, wild boars, camels, bats, and goats [ 8 , 9 , 14 , 18 , 54 , 55 , 57 , 58 ]. While dromedary camels were reported to be infected with HEV genotype 7 [ 14 , 15 ], their potential to transmit the infection to humans was only reported in a single case from the United Arab Emirates [ 10 ]. Recent HEV seroprevalence and genetic characterization studies in dromedary camels from Saudi Arabia [ 15 , 29 ] show an overall seroprevalence of 23.1% with slightly lower prevalence in imported camels compared to domestic camels (22.4% vs. 25.4%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for HEV zoonotic transmission by ingestion of uncooked swine, wild boar or deer meat products have been well documented [ 23 , 116 , 117 , 118 , 119 , 120 ]. Among ruminants, in addition to cluster cases directly linked to the consumption of raw deer meat, there is growing evidence on the role of domestic camels as zoonotic sources of HEV gt7 infection [ 121 ], as indicated by a case of chronic hepatitis E after transplantation in a patient from the United Arab Emirates who regularly consumed camel milk and meat [ 20 ]. Human HEV infections associated with consumption of products from domestic cattle, goats and sheep have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%